2020
DOI: 10.1101/2020.01.10.901587
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ephrin-B2 Paces Neuronal Production in the Developing Neocortex

Abstract: ABSTRACTBackgroundDuring mammalian cerebral cortex development, different types of projection neurons are produced in a precise temporal order and in stereotypical numbers. The mechanisms regulating timely generation of neocortex projection neurons and ensuring production in sufficient numbers of each neuronal identity is only partially understood.ResultsHere, we show that ephrin-B… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…The rabbit polyclonal anti‐TBR1 was raised against amino acids 50–150 of mouse TBR1(Abcam 31940, ). It is a widely used antibody to detect TBR1 in the mouse neocortex (Kischel et al., 2020; Ratie et al., 2020 Woodworth et al., 2016). The pattern of immunostaining we observed was similar to previously published immunostaining of TBR1.…”
Section: Methodsmentioning
confidence: 99%
“…The rabbit polyclonal anti‐TBR1 was raised against amino acids 50–150 of mouse TBR1(Abcam 31940, ). It is a widely used antibody to detect TBR1 in the mouse neocortex (Kischel et al., 2020; Ratie et al., 2020 Woodworth et al., 2016). The pattern of immunostaining we observed was similar to previously published immunostaining of TBR1.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, to compare our data to previously published data collected by counting cells on tissue section (2D method), we surveyed 7 previously published studies (Alsiö et al, 2013;Fei et al, 2014;Kischel et al, 2020;Knock et al, 2015;Lanctot et al, 2017;Postel et al, 2019;Wang et al, 2016;Yoon et al, 2017) and collected reported cell numbers at the 7 developmental stages (Sup Table 1). Graphical representation of the data (Sup Figure 3B) shows overall conservation of the profiles for each of the 4 cell populations with some differences, specifically in the number of Tbr2+ progenitors.…”
Section: Absolute Numbers Of Progenitor and Neuron Populations In Thementioning
confidence: 99%